Analysis of the spillover effects of green organic transformation on sustainable development in ethnic regions’ agriculture and animal husbandry - Luo Zhuo; Huang Yongxin (Open Geosciences)
This study focuses on the sustainable development of agriculture and animal husbandry in ethnic minority regions of China, particularly examining the impact of green organic transformation. Given the increasingly severe global environmental issues, there is growing societal demand for sustainability in agriculture and animal husbandry. Ethnic minority regions face unique challenges and opportunities due to their distinct geographical, environmental, and cultural contexts. Therefore, it is crucial to investigate in depth the effects of green organic transformation on the sustainable development of agriculture and animal husbandry in these regions. Using panel data from 2013 to 2022, this study measures the Agriculture and Animal Husbandry Sustainable Development Index (ASDI) in eight ethnic minority provinces. It comprehensively evaluates sustainability from both overall and detailed perspectives. By constructing a panel threshold model, the study further explores the spillover effects of green organic transformation on the sustainable development of agriculture and animal husbandry in ethnic minority regions, informing targeted policies and strategies. The research indicates that green organic transformation has significantly positive effects on the sustainable development of agriculture and animal husbandry. We will innovate and extend the agricultural and animal husbandry industry chain, increase training for farmers and herdsmen, improve their feasible ability to make green organic transformation, and build an agricultural and animal husbandry development platform of “cooperatives + markets + farmers.” This supports high-quality development in agriculture and animal husbandry in ethnic minority regions. However, the study has limitations such as the time span and sample size of the data, which may constrain the generalizability of the results. Additionally, further research is needed to deepen the understanding of the specific mechanisms of green organic transformation. Future studies should expand the sample size, increase the length of time series, and integrate qualitative analysis methods to comprehensively understand the intrinsic mechanisms of green organic transformation on the sustainable development of agriculture and animal husbandry in ethnic minority regions.